Remaja dan Post a Picture (PAP) Media Sosial: (Suatu Kajian Psiko-Pastoral terhadap Remaja) - Lokollo, Valenchiend M.T; Ruimassa, Aleta Apriliana (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
Teenage is the one of the period of life span of human being. The teen itself refers to an individual that has been through a transition phase from childhood to adult. This phase is also well known as the time for the person who is looking for their real identity, and so that this stage is also vulnerable for the teens because potentially full of problems. Whether the individual success or not to be a healthy adult, mentally and physically, depends on how he/she is coping with the problems. Technology and communication development, uninevitably, bears what we called social media. The youth always use it to communicate one to another, and also to actualize themselves by using the features that is offered by the social media, for an instance share the picture and video. There is a terminology that depicts the activity of sending or receiving the photos, known as “post a picture” (PAP). This activity has a good impact yet the negative. It has been misused by teens by using it to send the porn picture or video. Undeniably, it becomes a big problem that the youth must face it, and surely it has an impact for the teen’s development. This young people becomes more vulnerable to do the “negative post a picture”. Hence, teenager must be helped to know how to deal with thast issue. A literature review is used to make a description about the data of the negative PAP, and to analyze teenage’s development from development psychology approach. This study found that a pastoral care for the youth that emphasize openness yet critics for the using of social media as a reflection as well as an action.